(untitled) (Research, Society and Development, 2020)
At a time when the world was affected by Covid-19, the number of fake news that circulate daily in the media has been influencing a large part of the population, making the discussion about the role of Science currently indispensable. This table highlights the importance of Scientific Dissemination as a support for the scientific literacy movement, which may allow a greater identification of unfounded news. The scientific dissemination since the first efforts towards their practices keeps a close dialogue with scientific literacy and contributes to the fight against “belligerent obscurantism”, a term created by Newton Duarte (2018) and the pseudoscience that spreads through several social media, fueled by fake news. It is through the cultural democratization of science that a better understanding of what is important for access to health, citizenship and political engagement will be provided. Thus, as it is a recent and extremely important topic, this exploratory work, supported by bibliographic research, aims to gather and present relevant points in the role of Scientific Dissemination that can help to reduce the impact of fake news.